Autologous Dendritic Cells Prolong Allograft Survival Through Tmem176b‐Dependent Antigen Cross‐Presentation. Issue 5 (14th April 2014) - Segovia, M.; Louvet, C.; Charnet, P.; Savina, A.; Tilly, G.; Gautreau, L.; Carretero‐Iglesia, L.; Beriou, G.; Cebrian, I.; Cens, T.; Hepburn, L.; Chiffoleau, E.; et al.
<x xml:space="preserve">Abstract</x> The administration of autologous (recipient‐derived) tolerogenic dendritic cells (ATDCs) is under clinical evaluation. However, the molecular mechanisms by which these cells prolong graft survival in a donor‐specific manner is unknown. Here, we tested mouse ATDCs for their therapeutic potential in a skin transplantation model. ATDC injection in combination with anti‐CD3 treatment induced the accumulation of CD8+CD11c+ T cells and significantly prolonged allograft survival. TMEM176B is an intracellular protein expressed in ATDCs and initially identified in allograft tolerance. We show that Tmem176b−/− ATDCs completely failed to trigger both phenomena but recovered their effect when loaded with donor peptides before injection. These results strongly suggested that ATDCs require TMEM176B to cross‐present antigens in a tolerogenic fashion. In agreement with this, Tmem176b−/− ATDCs specifically failed to cross‐present male antigens or ovalbumin to CD8+ T cells. Finally, we observed that a Tmem176b‐dependent cation current controls phagosomal pH, a critical parameter in cross‐presentation. Thus, ATDCs require TMEM176B to cross‐present donor antigens to induce donor‐specific CD8+CD11c+ T cells with regulatory properties and prolong graft survival.